2004
DOI: 10.1177/003172170408600210
|View full text |Cite
|
Sign up to set email alerts
|

High School Career Exploration Programs: Do They Work?

Abstract: IGHT NOW, many schools are scrambling to comply with the requirements of the federal No Child Left Behind (NCLB) Act, and educators are seeking strategies to boost achievement and move more students into higher education or a promising career. Raising academic standards for all students is the right thing to do, but standards-based school reform sometimes seems to ignore the fact that many students are simply not engaged sufficiently by academic study. If allowed to remain unmoti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Work-based learning, which encompasses learning in the workplace through internships, apprenticeships, informal learning on the job, and other vocational-specific curricula, has engaged interest in many countries around the globe for its potential to facilitate transitions from school to work, to ensure that training is aligned with labor market needs, to provide opportunities for the ongoing development of transferrable skills to meet the needs of the changing workplace, and to help students understand and adapt to the realities of the workplace ( Falconer and Pettigrew, 2003 ; OECD, 2014 ; Hoffman, 2015 ). Although WBL programs are more often offered across higher education and vocational training, WBL has also demonstrated promise at the secondary school level as a model for connecting academic learning to work preparation, enhancing positive student attitudes, academic motivation and goal articulation for school and career, and equipping young people with both academic and non-cognitive work readiness skills for the transition from high school into meaningful work and life ( Visher et al, 2004 ; Blustein, 2006 ; Kenny et al, 2010 ; Bempechat et al, 2014 ; Quintini and Martin, 2014 ). WBL programs thus represent one youth setting that can potentially complement the academic learning environment to develop personal, social, and work readiness competencies.…”
Section: Introductionmentioning
confidence: 99%
“…Work-based learning, which encompasses learning in the workplace through internships, apprenticeships, informal learning on the job, and other vocational-specific curricula, has engaged interest in many countries around the globe for its potential to facilitate transitions from school to work, to ensure that training is aligned with labor market needs, to provide opportunities for the ongoing development of transferrable skills to meet the needs of the changing workplace, and to help students understand and adapt to the realities of the workplace ( Falconer and Pettigrew, 2003 ; OECD, 2014 ; Hoffman, 2015 ). Although WBL programs are more often offered across higher education and vocational training, WBL has also demonstrated promise at the secondary school level as a model for connecting academic learning to work preparation, enhancing positive student attitudes, academic motivation and goal articulation for school and career, and equipping young people with both academic and non-cognitive work readiness skills for the transition from high school into meaningful work and life ( Visher et al, 2004 ; Blustein, 2006 ; Kenny et al, 2010 ; Bempechat et al, 2014 ; Quintini and Martin, 2014 ). WBL programs thus represent one youth setting that can potentially complement the academic learning environment to develop personal, social, and work readiness competencies.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, work-based learning (WBL), including internships, apprenticeships, job shadowing, and vocational-specific curricula, is a promising model for offering beneficial work exposure, especially for those low-income youth who have limited access to a variety of career role models (Kenny, 2013). WBL programs are intended to offer learning experiences that connect academic learning to work preparation, foster positive attitudes about academic skills, and enhance goal articulation and motivation for school and career (Kenny, 2013; Visher, Bhandari, & Medrich, 2004).…”
mentioning
confidence: 99%
“…In support of these positive expectations, some research has documented links between student career development and school motivation and engagement among youth in WBL programs (Kenny, Blustein, Haase, Jackson, & Perry, 2006; Kenny, Walsh-Blair, Blustein, Bempechat, & Seltzer, 2010). Using a national data set, Visher, Bhandari, and Medrich (2004), for example, found that students who participated in a range of WBL programs were more likely to graduate from high school and attend college than comparable students who did not participate in WBL. For business school students, WBL experience is valued in developing communication and problem-solving skills (Falconer and Pettigrew, 2003).…”
mentioning
confidence: 99%
“…The career counseling usually takes 2-3 meetings and consists of diagnostics and follow-up consultations (Machajová and Sojčák 2011). Given the limited time of these sessions, it is impossible to use career exploration programs such as Career majors, Internship/Apprenticeship or Job shadow (Visher et al 2004), which are both demanding and time consuming. Therefore, the aim of this study was to create a new form of inexpensive, simple and less time-consuming simulation which would replace first-hand career-related experience.…”
Section: The Current Studymentioning
confidence: 99%